Smart Contracts in Increasing Sharia Compliance on Peer To Peer Lending Platforms in Sharia Fintech - Rezki Akbar Norrahman (PT. Banjarese Pacific Indonesia, 2025)
Sharia fintech is a digital financial innovation that integrates technology with sharia principles, one of which is through a Peer To Peer (P2P) lending platform. However, in practice, various sharia compliance issues are still found, such as the potential for usury, gharar, and non compliance with contracts. This is due to limited manual supervision and the complexity of digital transactions. This study aims to analyze the potential for implementing smart contract technology to improve sharia compliance on P2P lending platforms. Using a qualitative approach through literature studies, this article examines how smart contract characteristics such as transparency, automation, auditability, and resistance to manipulation can support the implementation of sharia contracts such as murabahah, mudharabah, and musyarakah. The results of the study show that smart contracts enable the automatic implementation of sharia compliant transactions, reject unauthorized processes, and provide an immutable blockchain based monitoring and reporting system. This potential makes it a strategic tool in building a more accountable, efficient, and trusted sharia fintech ecosystem. However, the implementation of this technology still faces challenges, such as limited regulations, the need for multidisciplinary human resources, and low digital sharia literacy. Therefore, collaboration between scholars, regulators, and technology developers is needed to ensure that the implementation of smart contracts is not only technically superior, but also in accordance with the maqashid sharia. This study recommends the development of prototypes and further empirical research as concrete steps for implementation.